2013
DOI: 10.1590/s1677-5538.ibju.2013.06.03
|View full text |Cite
|
Sign up to set email alerts
|

Controversial predictors of biochemical recurrence after radical prostatectomy: a study from a Latin American (Brazilian) Institution

Abstract: Purpose: To analyze controversial clinicopathologic predictors of biochemical recurrence after surgery: age, race, tumor extent on surgical specimen, tumor extent on needle biopsy, Gleason score 3 + 4 vs 4 + 3, and amount of extent of extraprostatic extension and positive surgical margins. Materials and Methods:The needle biopsies and the correspondent surgical specimens were analyzed from 400 patients. Time to recurrence was analyzed with the Kaplan--Meier curves and risk of shorter time to recurrence using C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
1
1
0
2
Order By: Relevance
“…However, most studies did not find a relationship between them. [28,29] Our study results were also similar. Although it was significant in univariate (p=0.006) analysis, it was insignificant in multivariate (p=0.496) analysis.…”
Section: Discussionsupporting
confidence: 83%
“…However, most studies did not find a relationship between them. [28,29] Our study results were also similar. Although it was significant in univariate (p=0.006) analysis, it was insignificant in multivariate (p=0.496) analysis.…”
Section: Discussionsupporting
confidence: 83%
“…A) Curva geral da sobrevida livre de recidiva bioquímica dos 177 pacientes estudados; B) Sobrevida livre de recorrência bioquímica associada ao estadiamento patológico TNM; C) Sobrevida livre de recidiva bioquímica associada à margem cirúrgica comprometia; D) Sobrevida livre de recidiva bioquímica associada ao comprometimento de vesículas seminais; E) Sobrevida livre de recidiva bioquímica associada à extensão extraprostática de seguimento, a recidiva bioquímica após tratamento cirúrgico para o câncer de próstata ocorreu em 44,1% dos casos, maior do que a ocorrência descrita em estudos semelhantes da literatura. Aguilera et al 12 reportaram 37,3% de recidiva bioquímica, enquanto outra série 13 com 400 pacientes submetidos à prostatectomia radical relatou taxa de 32%.…”
Section: Métodounclassified
“…In 2014, Wabinga et al[4] reported only 46% for the 5-year OS rate among patients with PCa. All the three studies did not include correlation of prognostic factors unlike for this study which included correlation of prognostic prognostic factors with OS rate.Patients with PCa in developed countries have better OS rate than the ones in developing countries[11][12][13][14][15][16]. In 2017 Ukawa et al reported a tremendous 3-year OS rate of 88.6% in patients with PCa in the BioBank Japan Project which included 4793 cases…”
mentioning
confidence: 99%